Effect of Health Education Based on the Information–Motivation–Behavioral Skills Model on Maternal Knowledge, Motivation, Skills, and Behavior in Stimulating Child Speech Development - Ida Nursanti; Bhisma Murti; Anna Kusumawati Sugiharti; Muhammad Erwan Syah (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: The primary education of children under the age of three is provided by caregivers, and mothers are the principal caregivers within the family. The key to optimizing child development lies in enhancing mothers’ ability to provide developmental stimulation. This study aimed to examine the effectiveness of health education based on IMB theory in improving mothers’ health behaviors related to speech development stimulation. Subjects and Method: The study employed a quasi-experimental pretest-posttest control group design. The intervention group received health education in stages over four weeks, whereas the control group received health education through standard health services provided by health personnel. Each group comprised 30 mother–child dyads with children aged 2–3 years, selected according to the inclusion criteria. Data analysis compared pre- and post-intervention score differences using Wilcoxon test with Stata 13. Results: The pretest–posttest score comparisons in the intervention group showed statistically significant results and medium effect sizes for information (r= 0.32; p= 0.014), motivation (r= 0.35; p= 0.007), skills (r= 0.37; p= 0.005), and maternal behavior (r= 0.34; p= 0.008). In the control group, the mean differences in pretest-posttest scores for all variables were not statistically significant: information (r= 0.22; p= 0.083), motivation (r= 0.10; p= 0.465), skills (r=0.08; p= 0.564), and maternal behavior (r= 0.05; p= 0.706). Conclusion: Structured and integrated interventions addressing informational, motivational, and behavioral skills components have been shown to be more effective in enhancing speech development stimulation in toddlers. Future research should emphasize the use of behavior-theory-based approaches in the development of early childhood health programs.